KETERLIBATAN KONSUMEN DALAM PEMBELIAN SEBAGAI - ZuIfia Abdussamad (JURNAL LEGALITAS, 2009)
Involvement of consumer in each purchasing decision would always colours in every election of product brand by bases consideration of benefit criterion with product characteristic becoming its alternative. Consumer usually stays in weak position. To protect consumer is required a set law order. Involvement of consumer is a best concept to be comprehended as function of object. situation that altogether that will constitute in so many action of consumer with reference to accomplishment of requirement